Comparison of the Anti-bacterial Efficacy of Saussurea costus and Melaleuca alternifolia Against Porphyromonas gingivalis, Streptococcus mutans, and Enterococcus faecalis: An in-vitro Study - Munerah S. BinShabaib; Shatha S. ALHarthi; Bashayer S. Helaby; Manar H. AlHefdhi; Afrah E. Mohammed; Kawther Aabed (Frontiers Media S.A., 2022)
The aim was to compare the in-vitro antibacterial effectiveness of two herbal extracts (a) Saussurea-costus (S. costus) and (b) Melaleuca-alternifolia (M. alternifolia) against Porphyromonas gingivalis (P. gingivalis), Streptococcus mutans (S. mutans) and Enterococcus faecalis (E. faecalis). Aqueous extracts from M. alternifolia were prepared by adding 2 grams of S. costus and M. alternifolia, respectively to 100 ml distilled water. Bacterial strains of P. gingivalis, E. faecalis and S. mutans were treated into 3 groups. In groups 1 and 2, bacterial strains were treated with aqueous extracts of S. costus and M. alternifolia, respectively. In the control-group, bacterial strains were exposed to distilled water. Antibacterial activity of the samples and nanoparticles was determined. The minimum-inhibitory-concentration (MIC) values were determined using the microdilution method. P < 0.01 was considered statistically significant. The MIC for all bacterial strains treated with S. costus was significantly higher than that of M. alternifolia (P < 0.001). There was no significant difference in MIC for strains of P. gingivalis, E. faecalis and S. mutans treated with S. costus. For bacterial strains treated with M. alternifolia, the MIC was significantly higher for P. gingivalis compared with E. faecalis and S. mutans strains (P < 0.01). There was no difference in MIC for E. faecalis and S. mutans strains treated with M. alternifolia. The in-vitro antibacterial efficacy of M. alternifolia is higher than S. costus against P. gingivalis, E. faecalis and S. mutans.